2023
DOI: 10.3390/ijms24044043
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence on Membrane Estrogen Receptors as Novel Therapeutic Targets for Central Nervous System Pathologies

Abstract: Nuclear- and membrane-initiated estrogen signaling cooperate to orchestrate the pleiotropic effects of estrogens. Classical estrogen receptors (ERs) act transcriptionally and govern the vast majority of hormonal effects, whereas membrane ERs (mERs) enable acute modulation of estrogenic signaling and have recently been shown to exert strong neuroprotective capacity without the negative side effects associated with nuclear ER activity. In recent years, GPER1 was the most extensively characterized mER. Despite tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 159 publications
0
10
0
Order By: Relevance
“…Although the link between rapid E2 signaling and behavioral control has not previously been described in gonadally intact female rodents, there is a rich literature detailing signaling mechanisms of membraneassociated ER signaling [87][88][89][90] . Here, we find that rapid E2 signaling at membrane-associated receptors promotes synaptic excitation of BNST CRF neurons that are required for motivated alcohol drinking and more engaged when females are in a high ovarian E2 state.…”
Section: Discussionmentioning
confidence: 99%
“…Although the link between rapid E2 signaling and behavioral control has not previously been described in gonadally intact female rodents, there is a rich literature detailing signaling mechanisms of membraneassociated ER signaling [87][88][89][90] . Here, we find that rapid E2 signaling at membrane-associated receptors promotes synaptic excitation of BNST CRF neurons that are required for motivated alcohol drinking and more engaged when females are in a high ovarian E2 state.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptors (ER) are located in the nucleus and consist of two types of classical nuclear receptors, ERα and ERβ, which mediate the effects of estrogen 204,205 . Studies have shown that ER is closely related to the occurrence and development of breast cancer, in which the overexpression of ER α (ER‐positive) accounts for 70% of breast cancer, 206 thus being a well‐established target for the treatment of breast cancer 207 .…”
Section: Vhl Ligands and Their Utilizations In Protacs For Cancer Dru...mentioning
confidence: 99%
“…Estrogen receptors (ER) are located in the nucleus and consist of two types of classical nuclear receptors, ERα and ERβ, which mediate the effects of estrogen. 204 , 205 Studies have shown that ER is closely related to the occurrence and development of breast cancer, in which the overexpression of ER α (ER‐positive) accounts for 70% of breast cancer, 206 thus being a well‐established target for the treatment of breast cancer. 207 Currently approved endocrine treatments for breast cancer include aromatase inhibitors (AIs), like letrozole, selective ER modulators (SERMs), like tamoxifen, and selective ER degraders (SERDs), like fulvestrant.…”
Section: Vhl Ligands and Their Utilizations In Protacs For Cancer Dru...mentioning
confidence: 99%
“…Accordingly, estradiol treatment of women that were exposed to interpersonal violence has been shown to attenuate negative effect of severe PTSD symptoms on fear habituation [e.g., 381 ]. Moreover, mERs are considered a novel treatment target for age-associated memory decline, stroke, and neurodegenerative diseases [e.g., 382 , 383 ].…”
Section: Sex Hormone Co-signalingmentioning
confidence: 99%